Pendampingan Pembuatan Nila Presto Sebagai Alternatif Peningkatan Harga Jual Kualitas Ikan Grade B Di UMK Uyung Sehati - Vita Yanuar (Pusat Riset dan Inovasi Nasional, 2024)
The Community Service (PKM) carried out by the author aims to train the community's abilities (especially MSEs) in making presto tilapia, increase innovation and diversification of presto processed foods and increase MSEs' income through diversity of production results. The method used is to provide education and practice to Uyung Sehati MSEs and Antakusuma University students. Education provided about Presto Tilapia Making as an Alternative to Increase the Selling Price of Quality Grade B Fish at Uyung Sehati UMK. Meanwhile, practice is making Nila Presto directly. This activity will be held on September 7 2023 starting at 08.00 WIB until finished. Location of activities at Micro and Small Enterprises (UMK) Uyung Sehati Jl. Swadaya RT.001 Sungai Kapitan Village, Kumai District, West Kotawaringin Regency. The results of the PKM show that the community and/or micro business actors have been able to make presto tilapia but still need assistance. Apart from that, the results of presto tilapia fish can be diversified into various flavors such as savory taste, white flesh color, soft texture with all parts edible, and a distinctive fish smell.